Tradução e adaptação transcultural da escala de apego Relationship Sscales Questionnaire (RSQ) para o português brasileiro - Assis, Eunice Neves de (2018)
The attachment pattern may play an important role in the expression of dementia symptoms, but for the progress of studies in this area attachment measurements adapted to the Brazilian elderly population are nedeed. This work documents the the Relationship Scales Questionnaire (RSQ) translation and the cultural adaptation process to Brazilian Portuguese. As a first step a translation was carried out following the guideline for translation and cultural adaptation of patient-reported outcomes measures proposed by the International Society for Pharmacoeconomics and Outcomes Research (ISPOR). In a second phase, the translated version was tested for content validation, internal consistency, test-retest stability, and association between personality and attachment factors, using a sample of 43 healthy elderly people enrolled in the Family Health Strategy program (ESF) ) of the city of Porto Alegre-RS / Brazil. Only 6 of the 30 items nedeed word or expression adaptations to keep the conceptual and semantic equivalence. The RSQ patient-reported format was not very suitable among the elderly with visual deficits and low schooling. Others RSQ translated versions, one for application by interview and another for use with informants, were developed. The scale presented good to moderate internal consistency in domains related to anxiety. Only the measure for secure attachment presented significant difference after the application of the retest and results of the association between personality factors approximated to those of previous studies. It is recommended to carry out more studies with samples of older adults, with a diverse socioeconomic profile and a shorter interval for test-retesting.